ANALISIS KUALITAS PELAYANAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA MOEDAL KOTA SEMARANG (Studi Kasus Wilayah Pelayanan Distribusi Reservoir Gajah Mungkur dan Kudu) - Listanti Listanti; Hesti Lestari; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2015)
Service quality is a benchmark of perfection and distinction of a service product provided by public service organization. The essence of a public service is providing excellent service to the community. One of the existing public service organizations is the Perusahaan Daerah Air Minum (PDAM) Tirta Moedal Semarang, which provide clean water for citizen of Semarang city. In assessing the quality of services provided by PDAM Tirta Moedal, there are some dimensions or dimensions that are used as benchmarks. These dimensions are tangible, realibility, assurance, responsiveness and accessibility. The result of this research shows that the quality of service for the major products of PDAM Tirta Moedal services as providers of clean water needs of society Semarang city thus getting less good judgment. It can be seen from the performance of service dimensions of service-related products such as clean water clean water quality, continuity of drainage, water discharge volume, ability Engineering Officer in repairs got under assessment weighting 250 which means less well. The level of compliance of the quality of service the PDAM Tirta Moedal to get the highest percentage is payment access customer accounts that is equal to 89.52%, and the lowest percentage that the quality of water obtained the percentage of 66,47%. The results of the overall study indicates the elements that need to be improved in order to improve the public services quality viewed from the priority improvements in quadrant A in the Cartesian Quadrant PDAM Tirta Moedal is the ability of technical personnel to repair, clean water quality, continuity drainage, drainage water debit volume, speed and responsiveness of technical personnel in performing repairs.